THE DETERMINATION OF INFORMATION AND ATTITUDES OF HEALTH INFORMATION TEACHER CANDIDATES ABOUT GENETICALLY MODIFIED ORGANISMS - Alan, Burcu; Yıldız, Selin; Zengın, Fıkrıye Kırbag (My University, 2019)
This study was conducted to determine the knowledge and attitudes of health information teachercandidates about genetically modified organisms. The study was conducted with 90 nurses in total,58 women and 32 men, who received formation training in the Faculty of Education of FiratUniversity, in the fall period 2017-2018. The scanning method was used in the study. The\"Genetically Modified Organisms Questionnaire\" which consists of 14 questions developed byDemir & Pala (2007) was used as data collection tool. SPSS package program was used to analyzethe obtained data. While 73.3% of the participants stated that they heard on television of the termGMO for the first time, 21.1% said that they heard it via internet. The number of participantsindicating that GMOs are needed to increase productivity in agriculture is 63.3%. 93.3% ofparticipants stated that GMO could create health problems. 83.3% of participants stated that theyread the label of the products in the shopping, 98.8% stated that products with GMOs should bementioned on the packages and 92.2% stated that they will not take these products if they arementioned on the package. While all of the candidates stated that they would not consume aproduct carrying a pig genes, 5.6% stated that they could consume a product carrying a humangenes. Among the products to be graded, the genetically modified tomato (1.21) received the mostnegative score while iron and beta carotene rich rice (1.88) had the highest score. In the light ofthese findings, it was concluded that health information teacher candidates lack information aboutGMOs and that their view to GMOs products is negative.
Keywords: Biyoloji; Biyoteknoloji ve Uygulamalı Mikrobiyoloji; Genetik ve Kalıtım